Global Retinoblastoma Presentation and Analysis by National Income Level - Global Retinoblastoma Study Group (2020)
Importance: Early diagnosis of retinoblastoma, the most common intraocular cancer, can save both a child's life and vision. However, anecdotal evidence suggests that many children across the world are diagnosed late. To our knowledge, the clinical presentation of retinoblastoma has never been assessed on a global scale.